An evaluation of knowledge of circular economy among Therapeutic Radiographers/Radiation Therapists (TR/RTTs): Results of a European survey to inform curriculum design. - Soares, A.L.; Buttigieg, S.C.; Couto, J.G.; Bak, B.; McFadden, S.; Hughes, C.; McClure, P.; Rodrigues, J.; Bravo, I. (Radiography, 2023)
Global warming and the increase in greenhouse gases are a current concern worldwide. The healthcare sector constitutes about 4.4% of all emissions. This study aims to evaluate the knowledge, awareness and attitudes of Therapeutic Radiographers/Radiation Therapists (TR/RTTs) regarding environment-related concepts to inform the development of educational curriculum. A validated self-designed survey was distributed to TR/RTTs across Europe by the SAFE EUROPE partners and via social media between October 2021 and February 2022. The survey was divided into six sections: (i) demographics, (ii) knowledge of Circular Economy (CE) and Green Skills (GS), (iii) personal attitudes, (iv) TR/RTTs attitudes, (v) the importance of CE, and (vi) education. Questions consisted of mostly Likert scales complemented with other closed- and open-ended questions. 31%–42% of participants are aware of national and departmental policies in CE and GS concepts. Even though half of the participants considered that they advocate and practice CE, the open questions indicated that participants only focus on waste management, ignoring all the other dimensions of CE in healthcare. Personal attitudes and lifestyles also did not reflect CE. TR/RTTs considered CE practices and GS development essential. However, the suggested academic level at which these skills should be developed was split between High School (44%) and Bachelor's degree (32%). It is essential to raise awareness among TR/RTTs about the various dimensions of CE applied to healthcare: "green transportation", "environment-friendly procurement", "hospital building design", "food process optimisation", "water reduction", "energy efficiency", and "waste management". These GS must be developed by TR/RTTs to decrease their impact on the environment. Their training may need to be lifelong, starting during basic high school education and continuing as healthcare professionals after graduation.